An unplanned life : a memoir - Elsey, George M., 1918-2015 (University of Missouri Press, 2005)
"Memoir of the author's experiences working in the White House during the Roosevelt and Truman administrations, including inside accounts of his work on classified documents, U.S.-Soviet relations, and Truman's "Whistle-Stop Campaign," and his long association with the American Red Cross"--Provided by publisher